Unintended Effects of Targeting an Environmental Rebate - Alpízar, Francisco; Nordén, Anna; Pfaff, Alexander; Robalino, Juan (Springer, Berlín (Alemania), 2020)
When designing schemes such as conditional cash transfers or payments for ecosystem services, the choice of whom to select and whom to exclude is critical.We incentivize and measure actual contributions to an environmental public good to ascertain whether being excluded from a rebate can affect contributions and, if so, whether the rationale for exclusion influences such effects. Treatments, i.e., three rules that determine who is selected and excluded, are randomly assigned. Two of the rules base exclusion on subjects’ initial contributions. The third is based upon location and the rationales are always explained. The rule that targets the rebate to low initial contributors, who have more potential to raise contributions, is the only rule that raised contributions by those selected. Yet by design, that same rule excludes the subjects who contributed the most initially. They respond by reducing their contributions even though their income and prices are unchanged.